Analisis tingkat pemahaman keselamatan berenang pada pengunjung kolam renang - Rumpoko, Satrio Sakti; Sistiasih, Vera Septi; Sunjoyo, Sunjoyo; Santoso, Slamet; Sholeh, Muchhamad; Rasyid, Anwar (Jurnal Porkes, 2023)
This study was conducted to determine how high the level of understanding of swimming safety in swimming pool visitors in Surakarta City. The purpose of this study was to determine the level of understanding of swimming safety in swimming pool visitors in Surakarta City. This research is a quantitative research with data analysis with percentage sescriptive. Data collection using questionnaires. This study focused the population on pool visitors in Surakarta City. This sampling technique is incidental, which is a sampling technique based on chance, that is, anyone who incidentally meets the researcher. The sample of this study was 24 people. The results of this study are described in percentage, namely the level of knowledge of swimming pool visitors about swimming safety in Surakarta City is categorized into 3 categories, including the "low" category as many as 3 people or 12.5%, for the "medium" category as many as 4 people or 16.7%, while for the "high" category as many as 17 people or 70.8%. Overall more than 50% of pool visitors in Surakarta City have a high level of understanding about swimming safety.